In situ SERS monitored photoactive yellow protein (PYP) chromophore model elimination, nano-catalyzed phenyl redox and I2 addition reactions. Issue 112 (22nd November 2016) - Li, Wei; Chu, Wenlei; Jin, Wen; Han, Xijiang; Ma, Yufei; Dai, Bin; Xu, Ping; Liang, Yuwei; Chen, Dengtai
Abstract : PhS nitration products absorbed on Ag/Au NPs underwent nitro- and amino-group redox cycle reactions monitored using SERS spectra. I2 addition to the CC double bond was also confirmed with SERS. Abstract : S -Phenyl-( E )-3-(4-hydroxyphenyl)prop-2-enethioate elimination, phenyl nitration, nitro reduction, amino oxidation and I2 addition to CC reactions were confirmed with surface-enhanced Raman scattering (SERS).